Associations between executive functioning, challenging behavior, and quality of life in children and adolescents with and without neurodevelopmental conditions - Thomas W. Frazier; Ethan Crowley; Andy Shih; Vijay Vasudevan; Arun Karpur; Mirko Uljarevic; Ru Ying Cai (Frontiers in Psychology, 2022)
The present study sought to clarify the impact of executive and social functioning on challenging behavior and the downstream influence of challenging behavior on quality of life and functioning in a large transdiagnostic sample. Understanding these relationships is crucial for developing and designing tailored intervention strategies. In a cross-sectional study, parent informants of 2,004 children completed measures of executive and social functioning, challenging behavior, child and family quality of life, and reported on functional impacts of challenging behavior. Using structural (path) modeling, analyses evaluated the associations between executive and social functioning, including emotion regulation and risk avoidance, with overall and specific types of challenging behavior. Structural models also examined the influence of challenging behavior on child and family quality of life, including measures of the immediate and extended environment, and functional impacts on the parent/child as well as interactions with the medical/legal systems. Finally, mediational models explored the direct and indirect effects of executive and social functioning on quality of life and impact measures via challenging behavior. Results indicated that executive functioning accounts for substantial variance (R2 = 0.47) in challenging behavior. In turn, challenging behavior accounts for substantial variance in child and family quality of life (R2 = 0.36) and parent/child impacts (R2 = 0.31). Exploratory mediational models identified direct effects from executive and social functioning measures on quality of life and functional impacts and indirect effects for executive functioning via challenging behavior. These findings support the development of new intervention strategies and suggest the need to measure executive functioning when assessing and tailoring the treatment of challenging behavior in clinical practice.